Development of Bola Tepak Game Model for Physical Education (PE) Instruction at Madrasah Tswanawiyah 1 Palembang - Adi Daya; Muhsana El Cintami Lanos; Ilham Arvan Junaidi (Universitas Negeri Semarang, 2026)
Physical education (PE) requires innovative and enjoyable learning models to improve students’ motor skills, motivation, and engagement. Traditional striking-based games are often less contextualized with students’ developmental characteristics, leading to limited skill acquisition and reduced participation. Therefore, this research aims to develop a Bola Tepak game-based learning model for PE instruction at Madrasah Tsanawiyah 1 Palembang and to describe its validity and practicality. This research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The participants included 7th-grade students as users and expert validators consisting of learning experts, content specialists, and media developers. Data collection techniques consisted of expert validation sheets, observation sheets, questionnaires, and field implementation tests. Validation results indicated that the model was feasible to implement, with an average score of 84% from learning experts, 86% from content experts, and 83.3% from media experts. Practicality testing involving students demonstrated positive implementation outcomes, with an average acceptance score of 88.1% and positive responses toward five game variations: Single Target Tepak, Chain Cone Tepak, Rolling Ball Tepak, Score Zone Tepak, and Team Relay Tepak. The findings show that the model enhances students’ striking skills, coordination, concentration, teamwork, and learning motivation. In conclusion, the Bola Tepak game-based learning model is valid, practical, and feasible to be used as an innovative and enjoyable alternative instructional strategy for PE.